Synthesis of trehalose-based chemical tools for the study of the mycobacterial membrane - Lesur, Emilie; Rollando, Paulin; Guianvarc’h, Dominique; Bourdreux, Yann (Comptes Rendus. Chimie, 2023)
Corynebacteriales including the causative agent of many diseases such as tuberculosis are known to be extremely resistant against external stress as well as to antibiotic treatments which is believed to be related to the singular architecture of their mycomembrane. Over the last decades, both bioorthogonal chemical reporters and fluorescent probes for the metabolic labeling of bacterial cell glycans were developed including several trehalose-based probes to study the dynamics of mycomembrane components. This review presents an exhaustive view on the reported syntheses of trehalose-based probes enabling the study of the mycomembrane biogenesis.